1993
DOI: 10.1111/j.1464-5491.1993.tb00029.x
|View full text |Cite
|
Sign up to set email alerts
|

An Evaluation of Bone Density and Turnover in Premenopausal Women with Type 1 Diabetes Mellitus

Abstract: Measurement of bone density and turnover was assessed in 20 premenopausal females with Type 1 diabetes mellitus and 27 age-sex-matched controls. Measurement was made of spinal (L2-4) and neck of femur bone density by dual-energy X-ray absorptiometry. L2-4 density was significantly higher in the diabetic patients compared with controls (1.224 +/- 0.021 g cm-2 vs. 1.161 +/- 0.020 g cm-2: p = 0.016). No significant difference was noted between the groups in neck of femur density. Measurement of bone formation was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
36
0
2

Year Published

2000
2000
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(40 citation statements)
references
References 26 publications
2
36
0
2
Order By: Relevance
“…In majority of earlier studies performed on type 1 diabetic population, both lumbar spine and hip BMD was decreased moderately. However, some studies reported normal hip BMD (22,23), and normal (24) or even increased spine BMD (25). Nevertheless, there is agreement that approximately 40-50% diabetic patients have decreased BMD and this decrease is independent of age, diabetes duration, presence of chronic microvascular complications, and the onset of diabetes (5,6,26), similar to our results.…”
Section: Discussionsupporting
confidence: 88%
“…In majority of earlier studies performed on type 1 diabetic population, both lumbar spine and hip BMD was decreased moderately. However, some studies reported normal hip BMD (22,23), and normal (24) or even increased spine BMD (25). Nevertheless, there is agreement that approximately 40-50% diabetic patients have decreased BMD and this decrease is independent of age, diabetes duration, presence of chronic microvascular complications, and the onset of diabetes (5,6,26), similar to our results.…”
Section: Discussionsupporting
confidence: 88%
“…Areal bone mineral density (aBMD) in young individuals with type I diabetes appear to be decreased in most (1)(2)(3)(4), but not all studies (5,6). In older patients with type I diabetes or insulin dependent diabetes a decreased bone density has been reported (7)(8)(9).…”
Section: Introductionmentioning
confidence: 99%
“…Reports concerning women with type II diabetes or non-insulin dependent diabetes have shown higher aBMD than controls without diabetes (10)(11)(12)(13)(14)(15), however not always significant (8,16) Bone turnover has been extensively studied in diabetic disease. In pre-menopausal diabetic women the disease is accompanied by a high bone turnover (1,3,5). In elderly women with type II diabetes or non-insulin dependent diabetes mellitus it has been reported that bone turnover is decreased (11,(17)(18)(19)(20), unchanged (16) or with a more mixed finding compared to in controls (13).…”
Section: Introductionmentioning
confidence: 99%
“…The Nord-Trodelag Health Survey (1) and the Iowa Women's Health Survey (2) found a 7-and 12-fold increase in hip fractures, respectively, in older type 1 diabetic women. Type 1 diabetes was associated with ϳ10% lower bone mineral density (BMD) compared with nondiabetic adults (3-10) in most but not all studies (11)(12)(13), though many include only small numbers of cases and lack adjustment for traditional osteoporosis risk factors (e.g., lower body weight and smoking). Few investigations (3,5,13) of type 1 diabetes and BMD focus exclusively on middleaged and postmenopausal women, those at highest risk for osteoporosis and fractures.…”
mentioning
confidence: 99%